Ensiklopedi ruang angkasa / Heather Couper dan Nigel Henbest ; penerjemah, Gunawan Admiranto ; editor, Lucia Indarwati, Victima Paska, Indah Sri Utami - COUPER, Heather; Henbest, Nigel; Gunawan Admiranto; Lucia Indarwati; Victima Paska; Indah Sri Utami (Kanisius, 2013)
303 hlm. : ilus. ; 28 cm